Reduced dietary intake of micronutrients with antioxidant properties negatively impacts muscle health in aged mice. Issue 1 (16th October 2017) - van Dijk, Miriam; Dijk, Francina J.; Hartog, Anita; van Norren, Klaske; Verlaan, Sjors; van Helvoort, Ardy; Jaspers, Richard T.; Luiking, Yvette
Abstract: Background: Inadequate intake of micronutrients with antioxidant properties is common among older adults and has been associated with higher risk of frailty, adverse functional outcome, and impaired muscle health. However, a causal relationship is less well known. The aim was to determine in old mice the impact of reduced dietary intake of vitamins A/E/B6/B12/folate, selenium, and zinc on muscle mass, oxidative capacity, strength, and physical activity (PA) over time. Methods: Twenty‐one‐month‐old male mice were fed either AIN‐93‐M (control) or a diet low in micronutrients with antioxidant properties (=LOWOX‐B: 50% of mouse recommended daily intake of vitamins A, E, B6, and B12, folate, selenium, and zinc) for 4 months. Muscle mass, grip strength, physical activity (PA), and general oxidative status were assessed. Moreover, muscle fatigue was measured of m. extensor digitorum longus (EDL) during an ex vivo moderate exercise protocol. Effects on oxidative capacity [succinate dehydrogenase (SDH) activity], muscle fibre type, number, and fibre cross‐sectional area (fCSA) were assessed on m. plantaris (PL) using histochemistry. Results: After 2 months on the diet, bodyweight of LOWOX‐B mice was lower compared with control ( P  < 0.0001), mainly due to lower fat mass ( P  < 0.0001), without significant differences in food intake. After 4 months, oxidative status of LOWOX‐B mice was lower, demonstrated by decreased vitamin E plasma levels ( P  < 0.05) and increased liver malondialdehyde levels ( P  = 0.018). PA was lower in LOWOX‐B mice ( P  < 0.001 vs. control). Muscle mass was not affected, although PL‐fCSA was decreased (~16%; P  = 0.028 vs. control). SDH activity and muscle fibre type distribution remained unaffected. In LOWOX‐B mice, EDL force production was decreased by 49.7% at lower stimulation frequencies ( P  = 0.038), and fatigue resistance was diminished ( P  = 0.023) compared with control. Conclusions: Reduced dietary intake of vitamins A, E, B6, and B12, folate, selenium, and zinc resulted in a lower oxidative capacity and has major impact on muscle health as shown by decreased force production and PA, without effects on muscle mass. The reduced fCSA in combination with similar SDH activity per fibre might explain the reduced oxidative capacity resulting in the increased fatigue after exercise in LOWOX‐B mice.